Physics ContributionsOriginal articleA comparative study of two reconstructive methods and different recommendations in intracavitary brachytherapy - Sresty, NVN Madhusudhana; Ramanjappa, Thogata; Rao, C. Ramakrishna; Raju, A Krishnam; Muralidhar, KR (Journal of Contemporary Brachytherapy, 2010)
Purpose : Intracavitary brachytherapy (ICB) is a widely used technique in the treatment of cervical cancer. In our Institute, we use different reconstructive methods in the conventional planning procedure. The main aim of this study was to compare these methods using critical organ doses obtained in various treatment plans. There is a small difference in the recommendations in selecting bladder dose point between ICRU (International Commission on Radiation Units & Measurements) -38 and ABS (American Brachytherapy Society). The second objective of the study was to find the difference in bladder dose using both recommendations. Material and methods : We have selected two methods: variable angle method (M1) and orthogonal method (M2). Two orthogonal sets of radiographs were taken into consideration using conventional simulator. All four radiographs were used in M1 and only two radiographs were used in M2. Bladder and rectum doses were calculated using ICRU-38 recommendations. For maximum bladder dose reference point as per the ABS recommendation, 4 to 5 reference points were marked on Foley’s balloon. Results : 64% of plans were showing more bladder dose and 50% of plans presented more rectum dose in M1 compared to M2. Many of the plans reviled maximum bladder dose point, other than ICRU-38 bladder point in both methods. Variation was exceeded in 5% of considerable number of plans. Conclusions : We observed a difference in critical organ dose between two studied methods. There is an advantage of using variable angle reconstruction method in identifying the catheters. It is useful to follow ABS recommendation to find maximum bladder dose.